2015
DOI: 10.20343/teachlearninqu.3.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Developing SoTL through Organized Scholarship Institutes

Abstract: The need to further integrate SoTL into college and university cultures has been discussed relatively frequently in recent teaching and learning literature. While a number of useful strategies to assist in this task have been advanced, one es pecially promising suggestion is the development of organized, institutionally recognized scholarship institutes. Centres or units of this sort have been created at higher education institutions in a number of countries, but little published infor mation currently exists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…• review the purpose and logistics of the program as a whole • share learning outcomes for all workshops • discuss approaches for engagement and networking • exchange ideas for resources and handouts The lessons learned from this study are pertinent to educational developers who are investigating how to advance a culture of educational research in postsecondary education. In the last five years, institutions have explored different techniques for engaging educators in the study of their own teaching, including scholarship institutes (Marquis, 2015), writing groups (Chitpin, 2011;Marquis et al, 2014;Pleschová & McAlpine, 2015), workshops (Weaver et al, 2013;Lawrence et al, 2016), and peer mentoring (Chitpin, 2011;Pleschová & McAlpine, 2015). These approaches collectively demonstrate the power of a community of practice to sustain engagement with the study of teaching and its potential to lead to change in teaching practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• review the purpose and logistics of the program as a whole • share learning outcomes for all workshops • discuss approaches for engagement and networking • exchange ideas for resources and handouts The lessons learned from this study are pertinent to educational developers who are investigating how to advance a culture of educational research in postsecondary education. In the last five years, institutions have explored different techniques for engaging educators in the study of their own teaching, including scholarship institutes (Marquis, 2015), writing groups (Chitpin, 2011;Marquis et al, 2014;Pleschová & McAlpine, 2015), workshops (Weaver et al, 2013;Lawrence et al, 2016), and peer mentoring (Chitpin, 2011;Pleschová & McAlpine, 2015). These approaches collectively demonstrate the power of a community of practice to sustain engagement with the study of teaching and its potential to lead to change in teaching practice.…”
Section: Discussionmentioning
confidence: 99%
“…Hubball, Clarke, and Poole (2010) examined how a certificate program produced leaders who could return to their home university and help establish a community of practice to offset many of the challenges in building capacity. Marquis (2015) describes the advent of scholarship institutes that operate apart from individual departments and serve as a leadership and support hub for educational research across a campus.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this gap, we undertook a study examining the design and the perceived benefits and limitations of SoTL institutes at research‐intensive universities worldwide. The results of this work, which have been described more fully elsewhere (Marquis ), provided a foundation upon which the scholarship component of MIIETL is currently being built. In this chapter, we outline some the steps taken to develop MIIETL's SoTL portfolio in the institute's first year, and provide preliminary evidence of the impact of those choices.…”
mentioning
confidence: 87%
“…Earlier research (Marquis ) indicated that effective SoTL institutes work to bring together and support a diverse range of scholars, creating a community of practice that both enhances the work conducted and helps individuals advocate for it within institutional cultures that can be unsupportive of teaching and learning inquiry (Mighty ). Nonetheless, this research also pointed out that such communities can be difficult to develop and sustain, particularly given demands on scholars’ time (Brew ) and the fact that SoTL is often not rewarded or recognized in considerations of career progress (Walker, Baepler, and Cohen ).…”
Section: The Establishment Of Miietl Research Fellowsmentioning
confidence: 99%
“…Many of these initiatives have at their core a desire not only to support individual SoTL scholars but also to embed teaching and learning inquiry within institutional contexts more broadly (Marquis, 2015;Williams et al, 2013). Contemporary SoTL support has sought to contribute to more thorough integration and uptake of SoTL by emphasizing alignment with institutional and disciplinary priorities, for example (Poole, Taylor, & Thompson, 2007;Schroeder, 2007), or advocating for high-level support and recognition of teaching and learning inquiry (Ginsberg & Bernstein, 2011;McConnell, 2012) (Simmons, 2016) documents several efforts designed to support and assess the embedding of SoTL within institutions across the country.…”
mentioning
confidence: 99%